Building a VoIP network with Nortel's multimedia communication server 5100 - Chafflin, Larry (Syngress Pub., 2006)
Provides information on deploying Voice Over IP (VoIP) products from Nortel Networks, the largest supplier of voice products in the world. This book presents a discussion of the various protocols used for transmitting converged data over IP, as well as an overview of Nortels hardware and software solutions for converged networks.